Dynamics of fluids im porous media - Bear, Jacob (Dover Publication / New York, 1972)
Contents: Introduction; Fluidos and porous propertics; Presure and piezometric head; The fundamental fluids transport equations in porous media; The equation of motion of a homogeneous fluid; Continuity and conservation equation for a homogeneous fluid